EFEKTIVITAS STRUKTUR PENGENDALIAN INTERN DENGAN MENGGUNAKAN PENDEKATAN COSO PADA SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) KOTA MANADO - Tamoding, Chandro Novrio; Ilat, Ventje; Kalalo, Meily (JURNAL RISET AKUNTANSI GOING CONCERN, 2018)
Internal control structure is a part of internal control that is always applied in various organizations in this case the secretariat of the regional peoples legislative assembly of Manado city implement internal control structure, and by using the COSO approach. The internal control structure using the COSO approach is needed to control the operational activities of the organization and aims to assess effectiveness based on the five elements of the COSO controlling component. The research method that used in this thesis research is descriptive method that is by collecting data from the research results and then describe it and attract a conclusions from the research, and the type of research used is qualitative descriptive. The results obtained that the internal control structure by using the COSO approach in secretariat of the regional peoples legislative assembly of Manado city is running effectively, and the implementation of internal controls in the control of COSO based on the five elements of control has been running effectively and show its effectiveness and and implemented in accordance with the procedures of internal control and the policy of the secretary of the regional peoples legislative assembly of Manado City.Keywords: Effectiveness, Internal Control Structure, COSO.